2010
DOI: 10.1074/jbc.m109.095232
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotectin D1 Induces Dephosphorylation of Bcl-xL in a PP2A-dependent Manner during Oxidative Stress and Promotes Retinal Pigment Epithelial Cell Survival

Abstract: Retinal pigment epithelial (RPE) cell integrity is critical for the survival of photoreceptor cells. Bcl-x L is a major anti-apoptotic Bcl-2 protein required for RPE cell survival, and phosphorylation of Bcl-x L at residue Ser-62 renders this protein pro-apoptotic. In this study, we identify serine/threonine protein phosphatase 2A (PP2A) as a key regulator of Bcl-x L phosphorylation at residue Ser-62 in ARPE-19 cells, a spontaneously arising RPE cell line in which Bcl-x L is highly expressed. We found that eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 54 publications
0
44
0
Order By: Relevance
“…PP2A, which is a ubiquitously expressed serine/threonine phosphatase, plays an important role in the regulation of cellular functions, including cell-cycle control and survival (28). Previous studies showed that PP2A dephosphorylated Bcl-2 family members, including Bcl-2 and Bcl-xL, and controlled its antiapoptotic activity (58,59). In this study, we showed that PP6, which belongs to the PP2A subfamily, played an important role in the regulation of Bcl-xL.…”
Section: Discussionmentioning
confidence: 63%
“…PP2A, which is a ubiquitously expressed serine/threonine phosphatase, plays an important role in the regulation of cellular functions, including cell-cycle control and survival (28). Previous studies showed that PP2A dephosphorylated Bcl-2 family members, including Bcl-2 and Bcl-xL, and controlled its antiapoptotic activity (58,59). In this study, we showed that PP6, which belongs to the PP2A subfamily, played an important role in the regulation of Bcl-xL.…”
Section: Discussionmentioning
confidence: 63%
“…These conditions are known to trigger apoptosis in other cell types, but normally the RPE appears to be resilient in part due to specific modifications of the apoptotic pathway. Our group 15 and others have shown that normal RPE has unusually low levels of caspase-8, 16 high levels of antiapoptotic Bcl-2 family proteins, 15,17 and neuroprotectin-D1, 18 all of which serve to inactivate proapoptotic and proinflammatory signaling pathways. We now seek to determine if these antiapoptotic conditions degrade during aging so that RPE cells become vulnerable to normal proapoptotic stressors, creating a tipping point beyond which retinal homeostasis is lost along with visual function.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to a previous study (25), PP activity was gradually decreased after HPO treatment and was significantly lower than that with vehicle treatment at 2 h (Table 1) Cells were pretreated with black soybean seed coat extract (BE, 50 mg/mL) for 2 h (22-0 h time points) and then treated with hydrogen peroxide (HPO, 500 mm) for 2 h (0-2 h time points). Data were normalized to protein concentrations, are expressed relative to the 22 h control and are presented as means6SEM of 6 replicates.…”
Section: Resultsmentioning
confidence: 66%